Psychological capital, quality of life, and well-being in mother caregivers of individuals with down syndrome - Chiracu, Alina; Cosma, Germina-Alina; Stepan, Amalia Raluca; Cosma, Marian Alexandru; Corlaci, Ionuț; Călugăru, Eleonora Daniela Ciupeanu; Voinea, Florin; Zăvăleanu, Mihaela; Burileanu, Horia Alin; Avramescu, Taina (Frontiers in Psychology, 2023)
Introduction Caused by an error in cell division that produces an additional chromosome 21, Down syndrome (DS) is one of the most common developmental disorders in the world. This study aims to analyze the relationship between psychological capital, quality of life and well-being of caregivers of individuals with Down syndrome (DS). Methods The participants were 98 caregivers (mothers, M = 52.13, SD = 11.39) of individuals with Down syndrome. The instruments used were the Psychological Capital Questionnaire (measuring self-efficacy, resilience, optimism, and hope), Quality of Life Questionnaire (including social support, general satisfaction, physical/psychological health, absence of excessive workload/free time), and Psychological Wellbeing Scale, investigating the following dimensions: self-acceptance, positive relationships with others, autonomy, environmental mastery, purpose in life, and personal growth. Results The mediation analysis showed that self-efficacy, hope, and resilience are positively associated to quality of life, and optimism is positively associated to well-being. The total effects of psychological capital on well-being are positive and significant and quality of life mediates the relationship between psychological capital and well-being. Discussion These results show that psychological capital is an important inner resource for caregivers of DS individuals and must be improved through support services, so that caregivers have a higher perception of the quality of life and implicitly of well-being.